2003
DOI: 10.1097/00005721-200309000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Care of Women With Gestational Diabetes

Abstract: The article reviews gestational diabetes mellitus, including etiology, diagnostic and screening criteria, risk factors, and care of the affected woman. Gestational diabetes mellitus affects approximately 7% of all pregnant women, resulting in more than 200,000 cases each year, and is defined as glucose intolerance that begins or is first recognized during pregnancy. Women are considered at high risk for gestational diabetes if they are markedly obese, have a personal history of gestational diabetes, have a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…GDM has adverse long-term consequences for both mother and offspring. Women with GDM have increased risk of developing GDM in a subsequent pregnancy [ 3 5 ] and type 2 diabetes within 5–10 years [ 4 ]. In addition, children born from pregnancies affected by glucose intolerance have higher risks for obesity and type 2 diabetes in early adult life [ 3 , 4 , 7 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDM has adverse long-term consequences for both mother and offspring. Women with GDM have increased risk of developing GDM in a subsequent pregnancy [ 3 5 ] and type 2 diabetes within 5–10 years [ 4 ]. In addition, children born from pregnancies affected by glucose intolerance have higher risks for obesity and type 2 diabetes in early adult life [ 3 , 4 , 7 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM), even when mild, can have adverse consequences on the health of both mother and child during pregnancy and early postpartum period [ 1 , 2 ]. Women with GDM have increased risk of GDM recurrence in subsequent pregnancies [ 3 5 ], and of overt type 2 diabetes mellitus [ 4 , 6 ], while infants born to mothers with GDM are at increased risk of developing obesity and diabetes in later life [ 7 ]. Studies have shown that screening, detection and management of GDM can mitigate the risk of adverse outcomes and metabolic diseases in both mother and child [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of diabetes during pregnancy is associated with maternal and fetal morbidities, including increased cesarean delivery rates due to perceived increased risks of cephalopelvic disproportion and macrosomia. 17,18 Importantly, the diagnosis of diabetes has been shown to lower a physician's threshold for performing cesarean delivery. 19,20 Some of the risk factors identified in this study and others are potentially modifiable, and such modification may have an impact on diabetes recurrence during a subsequent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a complication characterized by insulin resistance and glucose intolerance during pregnancy. GDM affects about 5%-13% of pregnancies in the United States; uncontrolled GDM can lead to serious adverse outcomes for the mother and fetus, such as difficult labor, hypertensive disorders, and preeclampsia, as well as neonatal hypoglycemia, respiratory distress syndrome, and macrosomia (Farrell, 2003;Simmons, 2011;Ryu et al, 2014). Historically, insulin has been the mainstay drug for the treatment of GDM.…”
Section: Introductionmentioning
confidence: 99%